Literacy Co-Teaching with Multi-Level Texts in an Inclusive Middle Grade Humanities Class: A Teacher-Researcher Collaboration - Chandler-Olcott, Kelly; Hinchman, Kathleen (Journal of Inquiry and Action in Education, 2015)
This article reports on a middle school literacy intervention implemented during a yearlong teacher-researcher collaboration. The purpose of this collaboration was to combine and adjust commonly recommended pedagogical approaches to address the literacy needs of a heterogeneous group of seventh graders attending an urban school. University researchers designed and implemented the intervention with an interdisciplinary team of three teachers. The intervention drew on sociocultural theories of language and learning. It had three main features: integration of English and social studies, multi-level texts, and co-teaching of heterogeneous groups. Qualitative data included field notes from classroom observations and planning meetings, transcripts from teacher interviews, and classroom artifacts. Data were analyzed as they were collected and used in planning sessions. Additional analysis after the intervention ended focused on exploration of critical events reflecting convergence and divergence of teachers' and researchers' perspectives on the intervention features. Findings were organized around three representative critical events, one per intervention feature. Implications of results for future middle grade co-teaching literacy interventions were explored.
Keywords: Affordances; Educational Research; Grade 7; Heterogeneous Grouping; Humanities Instruction; Interdisciplinary Approach; Intervention; Language Arts; Literacy Education; Middle School Teachers; Observation; Partnerships in Education; Qualitative Research; Reading Materials; Semi Structured Interviews; Social Studies; Special Education; Team Teaching; Urban Schools